Kemitraan Pemerintah-Swasta dalam Program Corporate Social Responsibility di Kabupaten Pasuruan - Magya Ramadhania Putri; Isnaini Rodiyah (Universitas Muhammadiyah Sidoarjo, 2016)
This research aims to describe community empowerment program synergistic held by local government of Pasuruan regency and the implementation of CSR program by PT HM Sampoerna Tbk in Sukorejo Sub-district, Pasuruan Regency, in addition to describe public-private partnership pattern between local government of Pasuruan regency and private sector. Descriptive type of research and qualitative method through in-depth interview, observation, and documentation were used in this thesis.Result of this research reveals the implementation of PPP with CSR basis between local governments of Pasuruan regency with PT HM Sampoerna Tbk is mutualism partnership. Yet, private sector is a dominant actor in this partnership, whilst local government of Pasuruan regency only play their role and function as regulator, namely to make local government regulation Number 31 Year 2012 about CSR. The lack of government's portion in running this partnership caused by the absence of CSR forum. Public-private partnership here belongs to pseudo partnership due to there are no any written agreements between local government and private sector.